Acute pulmonary complications following cosmetic hyaluronic acid dermal filler injections - Tan, Sin Nee; Huan, Nai-Chien; Hairudin, Khairee Aqil; Harun, Norra; Sivandan, Shobhana; Fauzee Andylim, Nizafaziasyida; Ibrahim, Aishah; Abdul Razak, Megat Razeem; Abdul Azih, Muhammad Naimmuddin (Wiley-Blackwell Publishing Ltd, 2025)
Hyaluronic acid (HA) injectable dermal filler is widely used in cosmetic procedures, but it rarely leads to pulmonary complications. We present four patients with acute pulmonary complications after HA filler injections: three with organising pneumonia and one with acute pneumonitis. All presented with dyspnoea and cough; three received bilateral breast injections, and one received both breast and buttock injections. All patients received supportive management, including oxygen therapy, corticosteroids, and empirical antibiotics, whereby three responded well, but one succumbed. Clinicians ought to be vigilant of potential life-threatening pulmonary complications related to HA filler injections, as most procedures are performed in unassuming healthcare settings where catastrophic complications are not anticipated.